Influence of peroxynitrite in gliding arc discharge treatment of alizarin red s and postdischarge effects - Abdelmalek, F; Merouani, DR; Ghezzar, MR; Semmoud, A; Addou, A; Brisset, JL (Industrial & Engineering Chemistry Research, 2013)
The gliding arc discharge is a cheap and efficient nonthermal plasma technique able to degrade organiccompounds dispersed in water at atmospheric pressure. Alizarin Red Sulfonate (ARS) is selected as a stable quinonic dye.Exposure of the dye solution to the discharge in a batch reactor induces two successive reaction steps according to the treatmentconditions. Direct exposure of the solution to the discharge induces simultaneous bleaching and COD evolution. Inpostdischarge conditions, that is, after the discharge is switched off, the reactions keep on developing. This study thus underlinestwo key features: the ability of glidarc discharges to degrade recalcitrant molecules and the low cost of the process which requiresshort exposure times. A model mechanism involves peroxynitrite as a likely active species formed in the discharge and involved inpostdischarge phenomena in aqueous solutions and suggests short exposure times and much longer postdischarge times foroptimized pollutant abatement.